The Vision of the Priestly Narrative: Its Genre and Hermeneutics of Time - Boorer, Suzanne (Ancient Israel and Its Literature, 2016)
Cover -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- The Structure of Pg -- The Genre and Hermeneutics of Pg -- The Paradigmatic Nature of the Scenarios within Pg's Story of the Nation and their Hermeneutics of Time -- The Interpretation of the Story of the Nation with Pg as a Whole, Its Trajectory, and Parallels, in Light of its Hermeneutics of Time -- Conclusion: Embodying the World of the Text, Cognitively, Existentially, and through Ritual Praxis, or Not -- Bibliography -- Index of Biblical References -- Index of Modern Authors